Construção de uma cartilha educativa sobre segurança do paciente na unidade de recuperação pós-anestésica - Viana, Maria Milaneide Lima (2022)
Introduction: Educational technologies help nurses to develop a differentiated view of patient safety and favor the teaching-learning process of professionals and patients/family members. Given the complexity that involves the perioperative period, more precisely the immediate postoperative period, strategies are needed to strengthen nursing care. Objective: To build an educational booklet for nurses on patient safety in the post anesthetic recovery unit. Method: Methodological study, developed from February 2021 to January 2022, consisting of two stages: the first stage integrative literature review, construction and validation of the appearance of an instrument for interviewing patients, application of the instrument with patients and the focus group with nurses, the second stage consisted of the development of an educational booklet on patient safety. Descriptive statistics and content analysis were used. Study approved under opinion No. 4,474,565. Results: With the integrative review, the modalities of educational technologies were found and the patient safety indicators were identified, which contributed to the construction of the instrument. The aforementioned instrument was validated by appearance, reaching a CVC of 0.94. After application of the instrument with the patients, it was observed that 66% were female, with elective surgeries (88.0%), gynecological surgeries (28.0%) and surgeries to remove cancerous nodules (20.0%), the safety indicators pointed out by the patients were the infrastructure, multidisciplinary team, family/caregiver and person/patient. A focus group was held with four nurses from the PACU, achieving the following results: safety indicators related to patient admission, procedures, scale, protocol and assessment/discharge. The educational booklet was built based on an integrative review, an interview with patients and a focus group with URPA nurses. Conclusion: the educational booklet for patient safety will support nurses in qualified and safe care in the post anesthetic recovery unit.